Processos de mediação docente e o desenvolvimento cognitivo dos estudantes em um clube de ciências: pontos de conexão entre a abordagem teórica de Reuven Feuerstein e o ensino de ciências por investigação - ALMEIDA, Willa Nayana Corrêa (Universidade Federal do Pará, 2023)
In this study, we investigate the problematic: In what terms are teacher mediation and students' cognitive development constituted with a view to structuring a new didactic environment in a Science Club, based on Reuven Feuerstein's theory and on the teaching of Science through investigation? For that, analyze teacher mediation processes and their effects on the cognitive development of students, establishing connection points between Reuven Feuerstein's theoretical approach and science teaching by investigation for the structuring of a new didactic space in the Science Club Prof. Dr. Cristovam W. P. Diniz. The constitution of the information to be analyzed took place in the aforementioned Science Club, which is configured as a space for non-formal education, from the application of the Investigative Teaching Sequence entitled “Sound Problem”. For organization and interpretation of the information collected, we chose to use microgenetic analysis. Research participants were eight students and three monitor teachers. During the analyzes carried out, it was possible to identify the use of various mediation purposes and criteria by the monitor teachers as each stage of the SEI was developed, in which the mediational teaching work was expanded or reduced according to the level of understanding and development of the students, as well as the situational variables that determine the difficulty and/or challenge of what was being proposed. These actions triggered speeches and attitudes on the part of students that evidenced the use of social practices of production, communication and knowledge assessment that allowed the development of cognitive functions, describing a profile of cognitive development of students. From these verifications, we structured the Modifying Investigative Environment, which can be seen as a new didactic space for the Science Club, in which the innovation lies in the intentional implementation of an investigational science teaching that promotes the cognitive and social growth of students. Thus, we understand that the Modifying Investigative Environment developed at the Prof. Dr. Cristovam W. P. Diniz from an investigative approach that presupposes the Mediated Learning Experience, can show a Structural Cognitive Modifiability of the students.